Determination of the number of ψ(3686) events at BESIII *Supported by the Ministry of Science and Technology of China (2009CB825200), National Natural Science Foundation of China (NSFC) (11235011, 11322544, 11335008, 11425524, 11475207), the Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program, the Collaborative Innovation Center for Particles and Interactions (CICPI), Joint Large-Scale Scientific Facility Funds of the NSFC and CAS (11179014), Joint Large-Scale Scientific Facility Funds of the NSFC and CAS (11179007, U1232201, U1532257, U1532258), Joint Funds of the National Natural Science Foundation of China (11079008), CAS (KJCX2-YW-N29, KJCX2-YW-N45), 100 Talents Program of CAS, National 1000 Talents Program of China, German Research Foundation DFG (Collaborative Research Center CRC 1044), Istituto Nazionale di Fisica Nucleare, Italy, Koninklijke Nederlandse Akademie van Wetenschappen (KNAW) (530-4CDP03), Ministry of Development of Turkey (DPT2006K-120470), National Natural Science Foundation of China (11205082), The Swedish Research Council, U. S. Department of Energy (DE-FG02-05ER41374, DE-SC-0010118, DE-SC-0010504), U.S. National Science Foundation, University of Groningen (RuG) and the Helmholtzzentrum fuer Schwerionenforschung GmbH (GSI), Darmstadt, WCU Program of National Research Foundation of Korea (R32-2008-000-10155-0). (February 2018) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Ai 艾, X. C. 小聪; Ambrose, D. J.; Amoroso, A.; An 安, F. F. 芬芬; An 安, Q. 琪; Bai 白, J. Z. 景芝; Baldini Ferroli, R.; Ban 班, Y. 勇; Bennett, J. V.; Bertani, M.; et al.
Abstract: The numbers of ψ(3686) events accumulated by the BESIII detector for the data taken during 2009 and 2012 are determined to be ( 107.0 ± 0.8 ) × 10 6 and ( 341.1 ± 2.1 ) × 10 6, respectively, by counting inclusive hadronic events, where the uncertainties are systematic and the statistical uncertainties are negligible. The number of events for the sample taken in 2009 is consistent with that of the previous measurement. The total number of ψ(3686) events for the two data taking periods is ( 448.1 ± 2.9 ) × 10 6 .